Project Report: An Investigation of +2 Level Students’ Concepts of Magnetism - Sharma, S. V. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
The present study entitled „An Investigation of +2 Level Students‟ Concepts of Magnetism‟ was administered to the students of +2 level learning concepts of magnetism. At the very outset, this study is a pilot study. Research tools were developed in workshop mode which comprises of conceptual multiple choice questions. To ensure the validity and reliability of the test each item was scrutinized in a brainstorming session of experts. The test was administered to +2 students of schools having well equipped facilities and devoted staffs dealing with physics education. Comprehensive analysis of the responses given by the students indicates a significant gap between the learning outcomes as expected from the curriculum given to the students and their real learning. It is suggested that a carefully planned instructions taking into consideration students‟ alternative frameworks may help to improve the state of affairs.